RETURN ON ASSETS, AND PROBLEMATIC FINANCING IN INDONESIAN FINANCIAL INSTITUTIONS DURING THE COVID 19 PANDEMIC - Willy Yusnandar (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to see the state of retrun on assets (ROA) and problematic financing in bank financial institutions.This was done, because of the spread of the Covid 19 virus which resulted in a significant decline in many sectors in Indonesia, one of which is the economic sector.The number of people affected by layoffs, as a result of the spread of covid 19, which of course made all companies suffer losses, and had to make company budgets more efficient, so the decision of the company was to lay off their employees.The research method used in this paper is simple quantitative, using a comparison between the year before and the current year of the spread of covid 19. The results obtained in the study show that conventional financial institutions retrun on assets (ROA) in this case banksNote that the impact of Covid 19 has decreased, compared to the previous year.Meanwhile, the ROA of sharia financial institutions, in this case sharia banks and sharia business units, has increased, when compared to the years before covid 19 and after covid 19. Non-performing loans in conventional financial institutions experienced a significant increase.For Non Performing Finance, Islamic financial institutions, experienced a decline.Keywords: ROA, NPL, NPF.